Dampak Konvergensi International Financial Reporting Standards (IFRS) terhadap Pembelajaran Akuntansi pada Perguruan Tinggi Swasta se-Kota Bandar Lampung - Dwitayanti, Yevi; Putra, Dedi (Jurnal Bisnis Darmajaya, 2015)
ConvergenceÂ  of IFRS (International Financial Reporting Standards) are adjusting domestic standards order in accordance with IFRS (International Financial Reporting Standards). IFRS (International Financial Reporting Standards) using the concept of fair value , the implementation of the fair value, will certainly have an impact on learning accounting . This study aims to provide empirical evidence about the impact of the convergence of IFRS (International Financial Reporting Standards) to accounting learning at private university in the city of Bandar Lampung. The data are collected by questionaires to the respondents, they are accounting lecturer who taught courses in financial accounting at private university in the city of Bandar Lampung . . The sample is taken by Proportional random sampling method. Based on the method, we get 197 questionaires. A simple linear regression is employed as analitical technic. It is applied by using 17th SPSS. The results shows that there is no influence between convergence of IFRS (International Financial Reporting Standards) to the accounting learning. This can occur due to the convergence of IFRS (International Financial Reporting Standards) in Indonesia has implemented in early 2012, while the research was conducted in the year 2013. The time is not too long causes the academics do not understand completely about the convergence of IFRS (International Financial Reporting Standards) in Indonesia, so it has not been applied to the optimum in the accounting learning process.Keywords -International Financial Reporting Standards , accounting learning